Osteonecrosis as the presenting feature in a child with acute lymphoblastic leukaemia - Lim Sern Chin (Academy of Family Physicians of Malaysia, 2021)
A seven-year-old girl presented with pain in multiple joints and constitutional symptoms over a period of four months. There were no significant clinical findings apart from joint tenderness. Blood test results did not indicate any specific pathology and initial radiology imaging was normal. Subsequent careful examination of her X-ray images led to an MRI of her left knee, which revealed acute osteonecrotic changes. A following whole-body MRI examination demonstrated multifocal bony lesions. Bone marrow examination conclusively diagnosed acute lymphoblastic leukaemia (ALL). Acute osteonecrosis has classically been described as a complication of treatment in children with ALL and has not been recognised as a presenting feature until recently.